Use of appropriate ratio of scum mixed with coffee residue as briquette derived fuel - Silapanuntakul, Suthep; Ninkranjanakun, Nuttawat; Inthorn, Duangrat; Pandii, Wongdyan (Asian Health, Science and Technology Reports, 2016)
Attempts to use of waste residue generated from production processes to energy have currently been increased. This research was conducted to study the production of briquette fuel from scum mixed with coffee residue in different ratios. Totally, eleven mixed ratios i.e., 100:0, 90:10, 80:20, 70:30, 60:40, 50:50, 40:60, 30:70, 20:80, 10:90 and 0:100 by weight were tested to find the most appropriate ratio in briquette fuel production. Data were analyzed to verify physical and fuel properties as specified by ASTM. Emission of air pollutant concentration from briquette combustion was also determined. The result showed that the ratios of 80:20, 70:30 and 60:40 were more appropriate use for further analysis of physical and fuel properties. Significant differences in compressive strength and shatter index were observed in the test (P< 0.05). In addition, significant differences were found in the ash content, volatile matter, fixed carbon, total sulfur and heating value (P< 0.05). The emission of air pollutants for the CO, CO2, SO2 and NO2 were lowest at the ratio of 80:20. Regarding the finding, the mixed ratio of 80:20 was appropriate for the application due to the significantly high compressive strength (0.325±0.02kg/cm2), shatter index (0.272±0.02), volatile matter (89.00+3.51%), heating value (6,725.30+9.38 kcal/kg) and low moisture content (4.00+0.20%). This appropriate ratio is suggested to be used for the production of briquette fuel.